One‐Pot Transfer Hydrogenation Reductive Amination of Aldehydes and Ketones by Iridium Complexes "on Water". Issue 40 (9th September 2020) - Ouyang, Lu; Xia, Yanping; Liao, Jianhua; Luo, Renshi
Abstract : An efficient and practical one‐pot transfer hydrogenation reductive amination of aldehydes and ketones with amines has been developed by using iridium complexes as catalysts and formic acid as hydrogen source in aqueous solution, providing an environmentally friendly methodology for the construction of a wide range of functionalized amine compounds in excellent yields (≈ 80 %‐95 %). This effective methodology can be scaled up to gram scale with 0.1 mol‐% catalyst loading and also be employed in the synthesis of medical substances such as Meclizine. Abstract : A practical reductive amination between aldehydes/ketones and amines for the construction of a variety of amine compounds in excellent yields was developed. Moreover, the attractive features of this transformation are simple operation, good functional group tolerance, and high catalytic efficiency. In addition, the application of this useful method to the synthesis of Meclizine is demonstrated.